2020
DOI: 10.2147/rru.s264237
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Prevalence of Detrusor Underactivity and its Symptoms Co-relation with Urodynamic Study Findings in Patients with Lower Urinary Tract Symptoms</p>

Abstract: This study determines the prevalence and clinical presentation of detrusor underactivity (DU) and its urodynamic characteristics in adult patients with lower urinary tract symptoms (LUTS). Patients and Methods: This retrospective study has reviewed the symptoms and urodynamic study (UDS) findings of 283 patients with LUTS. Chi-square analysis was used to present the prevalence of UDS characteristics in both sexes. Results: Out of records of 206 patients included in this study, fifty-one (24.76%) patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Additionally, there are several downsides to UDS that should be considered before interpretation [ 19 ]. Also, there are no standard, detailed urodynamic definitions or diagnostic criteria for DU related to complex bladder pathophysiology [ 20 ]. This issue was a limitation of our study and a limitation of UDS in the diagnosis of LUTD.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there are several downsides to UDS that should be considered before interpretation [ 19 ]. Also, there are no standard, detailed urodynamic definitions or diagnostic criteria for DU related to complex bladder pathophysiology [ 20 ]. This issue was a limitation of our study and a limitation of UDS in the diagnosis of LUTD.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 ] This is more prevalent among institutionalized elderly patients. [ 6 ] Jeong et al . [ 7 ] showed that detrusor underactivity often coexists with other lower urinary tract dysfunctions.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluations for non-neurogenic LUTS detected UAB in up to 28% of males aged under the age of 50 years, and 48% of those over the age of 70 years. 6 Similarly, UAB was detected in up to 45% of females aged over 70 years. 6 Furthermore, DU has been attributed to both myogenic and neurogenic aetiologies and may no longer be exclusively associated with the aging population.…”
Section: Introductionmentioning
confidence: 95%
“…6 Similarly, UAB was detected in up to 45% of females aged over 70 years. 6 Furthermore, DU has been attributed to both myogenic and neurogenic aetiologies and may no longer be exclusively associated with the aging population. 7 The absence of DU pathogenesis research corresponds to current ineffective treatment options for UAB.…”
Section: Introductionmentioning
confidence: 95%